Rediscovering Blackstone: The influence of William Blackstone on the development of American legal science in the reception of Albert W. Alschuler - Sokalska, Edyta (The Opole Studies in Administration and Law, 2017)
The reception of common law in the United States was stimulated by a very popular and influential treatise Commentaries on the Laws of England by Sir William Blackstone, published in the late 18th century. The work of Blackstone strengthened the continued reception of the common law from the American colonies into the constituent states. Because of the large measure of sovereignty of the states, common law had not exactly developed in the same way in every state. Despite the fact that a single common law was originally exported from England to America, a great variety of factors had led to the development of different common law rules in different states. Albert W. Alschuler from University of Chicago Law School is one of the contemporary American professors of law. The part of his works can be assumed as academic historical-legal narrations, especially those concerning Blackstone: Rediscovering Blackstone and Sir William Blackstone and the Shaping of American Law. Alschuler argues that Blackstone’s Commentaries inspired the evolution of American and British law. He introduces not only the profile of William Blackstone, but also examines to which extent the concepts of Blackstone have become the basis for the development of the American legal thought.